2021
DOI: 10.1001/jamadermatol.2020.5394
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Usefulness and Recall of Sunscreen Label Information by Consumers

Abstract: 2019, the US Food and Drug Administration issued a proposed rule (84 FR 6204), an amendment to the Sunscreen Innovation Act of 2014, that would require listing active ingredients on the principal display panel of sunscreens to allow consumers to "more readily compare products and either select or avoid a given product accordingly." OBJECTIVE To understand consumers' perceived importance of active ingredients in sunscreen and their ability to recall these ingredients when comparing, avoiding, or selecting sunsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…A previous study found that only 28% of consumers found sunscreen ingredients to be important in sunscreen selection, especially those to avoid if there is concern about an unwanted ingredient 5 . The significant increase in chemical sunscreen search, from May 2021 to July 2021, coincides with the period when benzene was identified in some sunscreen and suncare products 6,7 . These findings, along with controversies on environmental and health impacts of UV filters, may have shifted consumer interest in tinted and mineral sunscreens as an alternative for chemical sunscreens.…”
Section: Sunscreen Type Search Period Notes 1a Vs 2b 2b Vs 3c 3c Vs 4...mentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found that only 28% of consumers found sunscreen ingredients to be important in sunscreen selection, especially those to avoid if there is concern about an unwanted ingredient 5 . The significant increase in chemical sunscreen search, from May 2021 to July 2021, coincides with the period when benzene was identified in some sunscreen and suncare products 6,7 . These findings, along with controversies on environmental and health impacts of UV filters, may have shifted consumer interest in tinted and mineral sunscreens as an alternative for chemical sunscreens.…”
Section: Sunscreen Type Search Period Notes 1a Vs 2b 2b Vs 3c 3c Vs 4...mentioning
confidence: 99%
“…5 The significant increase in chemical sunscreen search, from May 2021 to July 2021, coincides with the period when benzene was identified in some sunscreen and suncare products. 6,7 These findings, along with controversies on environmental and health impacts of UV filters, may have shifted consumer interest in tinted and mineral sunscreens as an alternative for chemical sunscreens. As the photobiological effects of visible light (VL) become to be better understood and as tinted sunscreens are the only products available to protect against VL, it is plausible to hypothesize that the photoprotective effects against VL may also have contributed to the increased public interest in tinted sunscreen.…”
mentioning
confidence: 99%
“…In this study, we examined the utility of image‐based and GIF‐based visual aids for the estimation of sunscreen quantity. This study was part of a larger study examining consumer interpretation of sunscreen labels 12 …”
Section: Introductionmentioning
confidence: 99%
“…In this issue of JAMA Dermatology , Tribby and colleagues evaluate how the proposed revisions may affect labeling. The authors explore the usefulness of listing the active ingredients on the principal display panel and the ability of study participants to recall these ingredients when selecting sunscreen products.…”
mentioning
confidence: 99%
“…Only 1 of the 47 participants in the study by Tribby and colleagues looked at the label to seek environmentally safe ingredients . The main reason for environmental concern is the association found between the active ingredients in sunscreen and coral reef bleaching, with oxybenzone being the most widely discussed UV filter .…”
mentioning
confidence: 99%